Segregacja medyczna poszkodowanych w obliczu zdarzeń masowych i katastrof = Medical segregation harmed in the face of mass events and disasters - Sowa, Magdalena; Winnicki, Andrzej; Tarkowski, Michał; Saletnik, Łukasz (Journal of Education, Health and Sport, 2015)
Sowa Magdalena, Winnicki Andrzej, Tarkowski Michał, Saletnik Łukasz. Segregacja medyczna poszkodowanych w obliczu zdarzeń masowych i katastrof = Medical segregation harmed in the face of mass events and disasters. Journal of Education, Health and Sport. 2015;5(10):43-50. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.31922 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2810%29%3A43-50 https://pbn.nauka.gov.pl/works/647898 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.08.2015. Revised 05.09.2015. Accepted: 29.09.2015. Segregacja medyczna poszkodowanych w obliczu zdarzeń masowych i katastrof Medical segregation harmed in the face of mass events and disasters Magdalena Sowa1, Andrzej Winnicki2, Michał Tarkowski3, Łukasz Saletnik1 1Katedra i Zakład Laseroterapii i Fizjoterapii, Uniwersytet Mikołaja Kopernika w Toruniu, Collegium Medicum w Bydgoszczy 2Katedra Technologii Postaci Leku, Uniwersytet Mikołaja Kopernika w Toruniu, Collegium Medicum w Bydgoszczy 3Wojewódzka Stacja Pogotowia Ratunkowego w Bydgoszczy mgr Magdalena Sowa Katedra i Zakład Laseroterapii i Fizjoterapii Uniwersytet Mikołaja Kopernika w Toruniu Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy ul. Marii Skłodowskiej – Curie 9 85 – 094 Bydgoszcz e – mail: magdalena.sowa@cm.umk.pl Streszczenie Częstotliwość zdarzeń masowych i katastrof bez wątpienia ma związek z rozwojem cywilizacji. Na współczesnym, zaawansowanym poziomie rozwoju medycyny, funkcjonalność Zintegrowanego Systemu Ratownictwa Medycznego w obliczu zdarzeń masowych i katastrof nadal stanowi ogromne wyzwanie. Duża ilość poszkodowanych oraz ograniczone zasoby sił i środków, zmuszają do zmiany sposobu postępowania ratowniczego. W zdarzeniach, których skutkiem jest duża liczba osób potrzebujących pomocy, jednym z najistotniejszych elementów jest segregacja medyczna, której celem jest zrobienie jak najwięcej, dla możliwie jak największej liczby poszkodowanych, w jak najkrótszym czasie. Słowa kluczowe: zdarzenie masowe, katastrofa, segregacja medyczna. Abstract The frequency of mass events and disasters undoubtedly has to do with the development of civilization. In today's advanced level of development of medicine, the functionality of the Integrated Medical Rescue System in the face of mass events and disasters remains a major challenge. A large number of victims and the limited resources of manpower and resources, forced to change its practice rescue. In events that result in a large number of people in need of help, one of the most important elements is Triage, whose aim is to do as much as possible for the greatest possible number of victims, as soon as possible. Keywords: mass event, disaster, triage.